AN EVALUATION OF LESOTHO’S RIGHT TO “EXPROPRIATE” THE WATER IN THE TREATY ON THE LESOTHO HIGHLANDS WATER PROJECT IN A “CONFLICT OF USES”* - Clive Vinti (Obiter, 2022)
This article explores the contemporary spectre of “expropriation” within the framework of the Treaty on the Lesotho Highlands Water Project (LHWP). The LHWP is an enigma in both its scope and practical application since it is governed by two apparently complementary treaties, and it seemingly incorporates the domestic laws of both South Africa and Lesotho. This is compounded by the contradictory legislation that has been promulgated by Lesotho that prioritises its domestic water uses despite the entrenched provisions of the LHWP regime that prioritises the supply of water to South Africa. This uncertainty has significant implications for a “conflict of uses” in the LHWP that may trigger an expropriation bid by Lesotho. This article unmasks the possible response of the LHWP legal framework to Lesotho’s right to “expropriate” the water in the LHWP in light of this ambiguous and confounding legal framework.